1987
DOI: 10.1159/000215558
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Deep Venous Thrombosis with a Very Low Molecular Weight Heparin Fragment (CY 222)

Abstract: Thirty patients presenting with phlebographically confirmed deep venous thrombosis were treated with a very low molecular weight heparin fragment (CY 222) in an open and prospective phase-2 trial. A uniform dosage of 750 IC anti-factor Xa units/kg/day was administered subcutaneously for 10 days or more to patients whose thromboses were categorized as postsurgical (17 cases) or medical (13 cases). The clinical symptoms of venous thrombosis diminished in 93% of the patients overall. The extent of vascular cleari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…The successful clinical use of heparin and its LMW derivatives necessitates moni toring of their activities with sensitive labo ratory assays [9][10][11][12], Heparin is usually measured by aPTT and TCT tests. Because heparin possesses both anti-Xa and anti-IIa activities, it can also be quantitated in plasma by chromogenic substrate methods involving the inhibition of extraneous fac tor Xa or thrombin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The successful clinical use of heparin and its LMW derivatives necessitates moni toring of their activities with sensitive labo ratory assays [9][10][11][12], Heparin is usually measured by aPTT and TCT tests. Because heparin possesses both anti-Xa and anti-IIa activities, it can also be quantitated in plasma by chromogenic substrate methods involving the inhibition of extraneous fac tor Xa or thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…LMW heparins are currently tested for prophylaxis and treatment of thromboembo lism [9][10][11][12], LMW heparins specifically in hibit factor Xa by binding to antithrombin III. In contrast, aPTT and thrombin are inac tivated poorly by these agents [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This activator binds to the thrombus immediately after its release and cannot be detected. 21 For CY 222, three test types can be identified: (1) In unmodified tests, antithrombotic activity was observed in vivo: APTT, TCT; (2) In modified tests, no statistical correlation to antithrombotic effect: Anti-Xa (HPT, HPC); t-PA. Still, the noncorrelation of t-PA can be an artifact insofar as a recent study 21 has shown that circulating t-PA can rapidly absorb to clots and then becomes undetectable;…”
Section: Discussionmentioning
confidence: 99%
“…24 ± 6 0.08 ± 0.08 0.08 ± 0.07 0.08 ± 0.08 0.08 ± 0.08 77 ± 28 0.80 ± 0. 21 12 ± 1 *Selection criteria, thrombus weight.…”
Section: Linear Correlationmentioning
confidence: 99%